Students’ Preferences of Interaction in Oral Productions - Dwi Dian Permata Sari; Abidin Pammu; M. Amir P (Hasanuddin University, 2022)
The objectives of the study were to know the students’ preferences of interactions in oral production at the fifth semester student in English Department of Makassar Muhammadiyah University. A descriptive method was applied to the fifth semester students as the sample of the study with the total number of samples were 24 students by using purposive sampling. The result of this study showed that there were three categories of preferences in oral interaction, those are preferences toward the teaching method, preferences toward the teacher performance, preferences toward the students’ interest. Meanwhile, the dominant preferences toward the teaching method were preferences of the open discussion class, the dominant preferences toward the teacher performance were preferences of the lecturer who help the students to solve the problem in the classroom, and the dominant preferences toward the students’ interest were preferences of using full English in presentation.